2019
DOI: 10.4274/tjo.galenos.2019.81594
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Dexamethasone Implant in the Treatment of Non-infectious Uveitis

Abstract: Objectives:To evaluate the long-term results of intravitreal dexamethasone implant (DEX) for noninfectious uveitis.Materials and Methods:The study included 62 eyes of 44 patients treated with DEX implant due to noninfectious uveitis and followed up for at least a year. Best-corrected visual acuity (BCVA), central foveal thickness, intraocular pressure (IOP), vitreous haze score, indications, immunomodulatory therapy and steroid usage before/after injection, number of injections, and adverse events were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…His symptoms partially improved on restarting oral steroids (10 mg prednisolone daily), pointing to an inflammatory cause of his visual symptoms. On the basis of this evidence, he was offered short-acting and long-acting intravitreal steroid implants, 22 (dexamethasone 0.7 mg and fluocinolone acetonide, respectively, Figure 1c ) to avoid chronic side effects of long-term systemic steroids. At the time of data cut-off, the patient remained disease free, with relatively minor persistent visual impairment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…His symptoms partially improved on restarting oral steroids (10 mg prednisolone daily), pointing to an inflammatory cause of his visual symptoms. On the basis of this evidence, he was offered short-acting and long-acting intravitreal steroid implants, 22 (dexamethasone 0.7 mg and fluocinolone acetonide, respectively, Figure 1c ) to avoid chronic side effects of long-term systemic steroids. At the time of data cut-off, the patient remained disease free, with relatively minor persistent visual impairment.…”
Section: Resultsmentioning
confidence: 99%
“… 7 As in our own series, most published series describe initial intervention with topical and/or oral corticosteroids. Although outcomes are generally good, with complete resolution of inflammation in most cases, some cases are recalcitrant, warranting alternative immunomodulatory agents, while peri-ocular or intravitreal steroids 22 have been employed as steroid-sparing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in VA and decrease in CMT and vitreous haze (VH) were observed in patients with NIUs treated with Ozurdex and followed up for at least 1 year [46]. In this study multiple injections yielded comparable visual and anatomical outcomes to single injections, and mean IOP did not change significantly during follow-up [46].…”
Section: Evidence Of the Efficacy Of Dex In Posterior Non-infectious mentioning
confidence: 56%
“…A significant increase in VA and decrease in CMT and vitreous haze (VH) were observed in patients with NIUs treated with Ozurdex and followed up for at least 1 year [46]. In this study multiple injections yielded comparable visual and anatomical outcomes to single injections, and mean IOP did not change significantly during follow-up [46]. The efficacy and safety of repeated DEX implants in patients with NIUs were further confirmed by several studies, with a median duration of therapeutic effect of 6 months and a transient rise in mean IOP always well managed by topical medication [46][47][48][49].…”
Section: Evidence Of the Efficacy Of Dex In Posterior Non-infectious mentioning
confidence: 99%
“…More recently, it has also been approved for the treatment of diabetic macular edema (DME). Numerous studies examining various numbers of DEX treatments and lengths of treatment have demonstrated its effectiveness at treating RVO, 1-5 uveitis [6][7][8][9][10] and DME. [11][12][13][14][15][16] As patients receive multiple DEX implants over extended lengths of treatment the concern grows for more significant intraocular pressure (IOP) elevations and cataract progression, both well-documented complications.…”
Section: Introductionmentioning
confidence: 99%